Body Mass Index and Grading Histopatologi Endometrioid Endometrial Carcinoma - Irwandi, Irwandi (Journal of Language and Health, 2024)
Endometrioid endometrial carcinoma is a malignant primary epithelial tumor in the endometrium, in the form of a glandular neoplasm with an acinar, papillary, or solid pattern, which can invade the myometrium. Histological grading is determined based on structural differentiation and cell atypia. Body mass index is calculated by dividing body weight by height in the square. The exact cause of endometrioid endometrial carcinoma is unknown. Still, most cases are associated with chronic estrogen stimulation of the endometrium, which triggers endometrial hyperplasia as a precursor to endometrioid endometrial carcinoma. Objective to assess the relationship between body mass index and histopathological grading of endometrioid endometrial carcinoma. Formalin-fixed paraffin tissue blocks from 31 patients with endometrioid endometrial carcinoma were used to examine the relationship between body mass index and histopathological grading. Baseline characteristics of the samples were obtained through medical records or pathology archives. The relationship between body mass index categories and histopathological grading was analyzed using the Kruskal-Wallis test. There was no significant relationship between body mass index and endometrioid endometrial carcinoma histopathological grading (p>0.05). The high body mass index category was not always associated with high histopathological grading of endometrioid endometrial carcinoma.